The Value of fantasy : the story of Hans Christian - Johnson, Spencer (La Jolla, CA : Value Comm., Inc Pub, 1979)
A brief biography of the 19th-century Danish author of many well-known fairy talesm which stresses the value of personal fantasies and imagination.
Keywords: Andersen, Hans Christian, 1805-1875; Author, Danish--19th century--Biography; Imaginations